Medical mistrust in racial minorities during the COVID-19 pandemic: Attitudes, actions and mental health outcomes. - Pei Wang; Yutong Zhu; Zexi Jin; Wisteria Deng (PLOS Global Public Health)
Numerous studies have demonstrated that minority groups had a higher level of medical mistrust than non-minority groups, and minority communities were criticized for noncompliance with the public health guidelines during the COVID-19 pandemic. This study explores racial minorities' attitudes and actual behavioral responses to the COVID-19 pandemic public health guidelines. A total of 221 adults responded to an online survey (mean age = 41.5; 48.0% female; 24.4% non-White). Study results indicate that racial minorities have lower trust in public health guidelines compared to non-minority groups but have taken more actions according to the public health guidelines. Analysis also uncovers the mediating roles of perceived pandemic severity and perceived public health action benefits, on the relation between minority status and public health compliance. This study contextualizes how racial minorities respond to public health crises in action, and the dissonance between that and their historical mistrust of medical authorities. This work highlights the importance of recognizing the minority's historical burden and fostering trust in government and professionals during public health crisis.